What is the solution to the following system of equations?
![What is the solution to the following system of equations class=](https://us-static.z-dn.net/files/d70/ae47154e7e6d90c19e8d068408974b02.png)
The solution to the following system of equations is:
(2,1)
We have a system of equation as:
[tex]y=6x-11--------------(1)[/tex]
and [tex]-2x-3y=-7------------(2)[/tex]
We solve following system of equation by the method of substitution.
We put the value of y in terms of x from equation (1) in equation (2)
[tex]-2x-3(6x-11)=-7\\\\\\i.e.\\\\\\-2x-18x+33=-7\\\\\\i.e.\\\\\\-20x+33=-7\\\\\\i.e.\\\\\\20x=33+7\\\\\\i.e.\\\\\\20x=40\\\\\\i.e.\\\\\\x=2[/tex]
and now on putting the value of x back in equation (1) we get:
[tex]y=6\times 2-11\\\\\\y=12-11\\\\\\y=1[/tex]
The solution is: (2,1)